UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS V MELALUI PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) - Viva Evita; Vicky Dwi Wicaksono; Ratna Dwi Herwiyanti; Selviari; Satrio Budiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low student learning result in mathematics learning are because students who feel mathematics is too boring may become disinterested when studying it in elementary school. The objective of this study is to evaluate how the Realistic Mathematics Education (RME) learning approach is applied to data presentation material and to identify areas that may enhance the learning outcome of class V students. Using a model created by Kemmis and McTaggart, This study employs the action research approach known as Participatory Action Research (PTK). Test sheets and response questionnaires are tools used to collect data. The participants of the study were thirty VA class students at SDN Dukuh Kupang III/490 Surabaya. An average of 0.58 was found based on cycle I data which was categorized as a moderate increase. On the other hand, in cycle II the average N-Gain value was 0.73, indicating a strong improvement classification. Researchers obtained a percentage of 94.4% from the student questionnaire responses following the application of Realistic Mathematics Education (RME) learning. It is known that the results of the teacher's answer questionnaire show a percentage of 95%. As a result, this calculation shows how well Realistic Mathematics Education (RME) is used. Based on the gathered data, this study establishes that the implementation of Realistic Mathematics Education (RME) may enhance student learning outcomes in the topic of data presentation for fifth-grade students in primary schools.